(untitled) (Web of Teachers: Inderscience Research, 2026)
This article focuses on a comparative linguostylistic analysis of traditional and contemporary features of press language in Uzbekistan and the Arab world. It highlights the considerable theoretical and practical value of the scholarly legacy of Mawarannahr linguists in the study of the Arabic language, as well as in maintaining and advancing cultural and intellectual traditions. Furthermore, the speeches of Abu Bakr al-Siddiq (may Allah be pleased with him) are examined from a linguostylistic viewpoint, considering them as exemplary models of journalistic discourse. The analysis demonstrates that his speeches possess essential features of publicistic style, such as persuasive power, expressiveness, clarity, simplicity, and a direct connection with the audience. The study also shows that these speeches played a crucial role in strengthening social unity, providing moral direction, and shaping public awareness. These characteristics reflect the functional and pragmatic nature of journalistic language and emphasize its significance as an influential tool in shaping social and ideological perspectives.